Femoral lengthening using the Precice intramedullary limb-lengthening system: outcome comparison following antegrade and retrograde nails. (September 2019) - Calder, Peter R.; McKay, Joseph E.; Timms, Anna J.; Roskrow, Tracy; Fugazzotto, Sharon; Edel, Penina; Goodier, W. D.
Abstract : Aims: The Precice intramedullary limb-lengthening system has demonstrated significant benefits over external fixation lengthening methods, leading to a paradigm shift in limb lengthening. This study compares outcomes following antegrade and retrograde femoral lengthening in both adolescent and adult patients. Patients and Methods: A retrospective review of prospectively collected data was undertaken of a consecutive series of 107 femoral lengthening operations in 92 patients. In total, 73 antegrade nails and 34 retrograde nails were inserted. Outcome was assessed by the regenerate healing index (HI), hip and knee range of movement (ROM), and the presence of any complications. Results: The mean lengthening was 4.65 cm (1.5 to 8) in the antegrade group and 4.64 cm (1.6 to 8) in the retrograde group. Of the 107 lengthenings, 100 had sufficient datapoints to calculate the mean HI. This was 31.6 days/cm (15 to 108). There was a trend toward a lower (better) HI with an antegrade nail and better outcomes in adolescent patients, but these were not statistically significant. Hip and knee ROM was maintained and/or improved following commencement of femoral lengthening in 44 patients (60%) of antegrade nails and 13 patients (38%) of retrograde nails. In female patients, loss of movement occurred both earlier and following less total length achieved. Minor implant complications included locking bolt migration and in one patient deformity of the nail, but no implant failed to lengthen and there were no deep infections. Three patients had delayed union, five patients required surgical intervention for joint contracture. Conclusion: This study confirms excellent results in femoral lengthening with antegrade and retrograde Precice nails. There is a trend for better healing and less restriction in hip and knee movement following antegrade nails. There are clinical scenarios, that mandate the use of a retrograde nail. However, when these are not present, we recommend the use of antegrade nailing. Cite this article: Bone Joint J 2019;101-B:1168–1176